The potential effect of instrumentation with different nickel titanium rotary systems on dentinal crack formation-An in vitro study - Fráter Márk Tibor; Jakab András; Braunitzer Gábor; Tóth Zsolt; Nagy Katalin (2020)
The potential mechanical impact of different rotary systems used for root canal preparation has been a matter of debate for long. The aim of this study was to explore the incidence of dentinal cracks after root canal instrumentation with various rotary systems, in vitro. One hundred and eighty intact lower central incisors were selected and randomly divided into fourteen treatment groups (n = 12/group) and a control group (n = 12). After decoronation, the root canals were instrumented with fourteen different rotary systems (E3, E3 azure, NT2, Hyflex CM, Hyflex EDM, 2Shape, OneCurve, ProTaper Next, ProTaper Gold, WaveOne Gold, Mtwo, Reciproc Blue, TF adaptive, K3XF). All roots were horizontally sectioned at 3, 6, and 9 mm from the apex with a low-speed saw under water-cooling. The slices were then examined under stereomicroscope for dentinal cracks. No cracks were found in the control group. Cracks were found in all treatment groups, predominantly in the 3 mm slices. There was no statistically significant difference in the number of cracks when comparing the different systems to each other at any section level. At 3 mm, however, five of the studied systems, namely K3XF (p = 0.004), Protaper Next (p = 0.001), Reciproc Blue (p<0.001), TF adaptive (p = 0.050), and 2Shape (p = 0.009) presented a significantly higher number of cracks than the control group. Within the limitations of this study, instrumented canals presented dentinal cracks, while uninstrumented ones presented no cracks after sectioning. There seems to be no significant difference among the tested systems regarding crack formation in the instrumented root canal wall. Crack formation occurred irrespective of the motion of the rotary system (rotational or reciprocation). Further studies are needed to clarify the factors that contribute to crack formation in the case of each individual rotary system.